Perspectives on Educational Leadership and Decision-Making in the Era of Digitalization - Sari, Puspita; Purba, Saut; Rangkuti, Irsan; Nasrun, Nasrun (Universitas Negeri Malang, 2023)
Changes in the digital era affect education. To synergize with change, educational leaders must be able to adapt. The problems presented are a research gap that will become a scientific discourse related to leadership perspectives and decision-making in the era of digitalization. The aim of the research will be limited to discussing the educational leadership model in the digital era, which is expected to be a solution to educational problems, and how the facts in the field describe the perspective of educational leadership in decision-making with the rise of digitalization. A deeper perspective of educational leadership related to the spirit of positive change in further educational improvement.The purpose of this research is to determine the model of educational leadership in the digital era and the perspective of educational leadership in decision-making with the rise of digitalization. This research is qualitative research using the literature study method. Literary sources are limited from the last four years, namely articles or writings published in 2019-2023. The results of this study found several models of leadership in the digital era, namely collaborative leadership, transformational leadership, democratic leadership, participatory leadership, and coercive digital leadership. Meanwhile, decision-making with a digitalization perspective is the use of educational data